Evaluación de un Shampoo a Base de Romero (rosmarinus officinalis) en Concentraciones al 10% y 20% como Antipulgas en Caninos Domésticos en la Clínica Veterinaria Mundo Animal. - Guamangallo Jácome, Geomara Estefanía (2019)
Rosemary (Rosmarinus officinalis) is an endemic plant from the Mediterranean, belongs to the family of Lamiaceae, highly prized for its antimicrobial, insecticidal, antioxidant and anti-inflammatory properties. This research was conducted at the Veterinary Clinic "Animal World", located in the canton Quito, Pichincha province, with the aim of evaluating a rosemary shampoo (Rosmarinus officinalis) in concentrations at 10% and 20% as flea in dogs domestic, for the execution of the investigation a population sample of 30 domestic canines taken, divided into 3 groups of 10 respectively for each treatment with a duration of 28 days; Before applying the treatment, a drawer test performed. Subsequently, baths were carried out to each experimental unit for four occasions with an interval of 7 days, on the 21st and 28th a flea population count was made to determine the efficacy and residual effect of treatments. By phytochemical analysis, the prevalence of the primary metabolites, such as phenolic compounds in 9.37%, and terpenoids, which shown in 2.67%, were determined. The results indicate that the T2 treatment (rosemary-based shampoo (Rosmarinus officinalis) at 20%) presented antiparasitic activity (fleas), with 100% reliability values, while the T1 treatment (rosemary-based shampoo (Rosmarinus officinalis) at (10%) showed an effectiveness of 19.9%, being the T3 treatment (1% propoxur-based shampoo) ineffective in the control of ectoparasites (fleas).